2019
DOI: 10.18203/2349-3933.ijam20195661
|View full text |Cite
|
Sign up to set email alerts
|

A study of etiological profile of acute confusional state

Abstract: Background: ACS (Acute confusional states) are on the rise taking the shape of an epidemic. These states are common among the elderly, but young individuals are also not spared. Prompt diagnosis and management of these states can decrease the associated morbidity and mortality.Methods: In this prospective observational study, etiological profile of ACS was evaluated in a total 100 patients, selected over a period of one year, after they fulfilled the CAM (Confusion Assessment Method) criteria.Results: Among 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A study by Rai et al mentioned that HTN was the most common (26.92%) associated condition followed by CVA with multiple infarct of four patients [13]. Kaur et al conducted a study and found that ACS was most common associated factor (85%), 19% were hypertensive, 17% had diabetes, CKD in 13%, CLD in 13%, drug abuse in 6%, malignancy 6%, and alcohol 4% [14]. Inouy et al study showed that common risk factor was visual impairment (RR-3.5), severe illness (RR-2.8), and high BUN (RR-2.0) [15].…”
Section: Associated Conditionsmentioning
confidence: 99%
“…A study by Rai et al mentioned that HTN was the most common (26.92%) associated condition followed by CVA with multiple infarct of four patients [13]. Kaur et al conducted a study and found that ACS was most common associated factor (85%), 19% were hypertensive, 17% had diabetes, CKD in 13%, CLD in 13%, drug abuse in 6%, malignancy 6%, and alcohol 4% [14]. Inouy et al study showed that common risk factor was visual impairment (RR-3.5), severe illness (RR-2.8), and high BUN (RR-2.0) [15].…”
Section: Associated Conditionsmentioning
confidence: 99%